Design of precursors and pH factors for enhancing the performance of nickel-based catalysts for anion exchange membrane water electrolysis - Eon-ju Park; Chiho Kim; Jooyoung Lee; Shin-Woo Myeong; Hoseok Lee; Sungjun Heo; Song Jin; Minjeong Park; Oi Lun Li; Sung Mook Choi (Electrochemistry Communications)
In response to the escalating global energy crisis and climate change, green hydrogen is increasingly recognized as a clean energy solution. This study presents an innovative approach to enhance the performance of nickel-based catalysts for anion exchange membrane water electrolysis (AEMWE) through careful selection of precursor materials and pH optimization in the co-precipitation process. By optimizing precursor types and pH conditions during co-precipitation synthesis, we achieved high yields of Ni(OH)2, which were then thermally treated to form NiO. Notably, the nitrate-based NiO (N-NiO) exhibited superior catalytic activity and durability, attributed to its favorable microstructure and charge transfer capabilities. In addition, to verify universality of the N-NiO study and to assess the water electrolysis performance, we synthesized a binary compound, nickel–cobalt oxide (NCO), by incorporating Co, and evaluated its electrochemical performance in an AEMWE single-cell system. The nitrate-based NCO-based single-cell achieved a high current density of 1.38 A/cm2 at 1.8 Vcell in 1 M KOH at 50 °C, with a low degradation rate of 23 mV/kh at 1 A/cm2 for 300 h. These findings provide valuable insights into the optimization of catalyst properties for hydrogen production and highlight significant commercial potential for hydrogen production and other electrochemical applications.